Perceptions of Violence in Universities: Contextual Panoramas - Oshiro Galindo, Julyana Sueme Winkler; Muleka Mwewa , Christian (Espergesia, 2025)
This paper aimed to present some theoretical-methodological reflections on perceptions of violence in the university context as indicated by the 202 participants enrolled in the III National Seminar and I International Seminar on Education and Culture for Teacher Training, which took place between May 18-28 and June 9, 2021. The data presented come from a survey collected through a questionnaire administered via Google Forms. The discussions were based on the theoretical framework of Critical Theory of Society. Considering ethical concerns, the information disclosed is organized as general data, without identifying individuals. Results indicated that the majority of participants were women; among those who self-identified as belonging to a social minority, the categories include: non-white women, immigrants, poor individuals, and residents of peripheral areas. Participants stated that they had witnessed or experienced violence within the university, often due to their minority status. The reported forms of violence included racism (22%), homophobia (18%), sexism (11%), age-related violence (11%), economic violence (10%), xenophobia (9%), violence against people with disabilities (7%), lesbophobia (6%), transphobia (3%), social violence (2%), and libophobia (1%).